Pengaruh Layanan Konseling Kelompok Teknik Assertive Training terhadap Disiplin Belajar Siswa Kelas X - Dewantari, Tri; Purnamasari, Veni (Psikopedagogia, 2017)
This study aimed to understand the effect of group counseling service in increasing students’ learning discipline. This was a quasi-experimental study with non-equivalent control group design. The subjects of this study were eighteen students taken by using purposive sampling technique. This study employed learning discipline rating scale to collect the data, while interviews and documentation were done as the supporting technique. The data analysis technique of this study was independent t-test by separate-variance t-test formula. The result of t-test score calculation by df=18 with the 0.05 significance level was 2.145, and the tcount = 6,652. Since tcount > ttable (6,652 > 2,145), it could be concluded that assertive training can increase the learning discipline on the students of Class X of SMK Trisakti Bandar Lampung. The result of this study provides an alternative solution for school counselor in facing the students who experience learning discipline problem through group counseling service.